Validasi Modul “GuLaLi” untuk Meningkatkan Keterampilan Guru Mengajar Siswa Tunarungu Perlindungan Diri dari Kekerasan Seksual - Febriana Ndaru Rosita; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Children with disabilities have three-time greater risk of child sexual abuse (CSA). Unfortunately, many teachers lack the skills to teach deaf students on sexual abuse and self-protection. This study examined the validity of a module (Gulati, Guru Latih Lindungi/ Teachers Train and Protect) to enhance the teachers' skills to train deaf students on CSA prevention. Prior to the study, the researcher developed the module following Behavior Skills Training (BST) procedure. Seven teachers from one of kindergarten and primary schools for the deaf in Bantul Regency participated in the study. The study used a one-group pre and posttest design. The data was quantitatively analyzed analysis was conducted through a statistical test using Wilcoxon signed rank test and also descriptive analysis. The result showed this module can improve teacher skills to teach the student how to prevent CSA (Z = -2.366, p<0.05).